Where Have All the Textbooks Gone? : Toward Sustainable Provision of Teaching and Learning Materials in Sub-Saharan Africa - Read, Tony (Washington, DC: World Bank, 2015)
This World Bank report is a rich compilation of information on teaching and learning materials (TLM) in Africa based on the extensive and multi-faceted experience of the author's work in the education sector in Africa. The study examines a wide range of issues around TLM provision including curriculum, literacy and numeracy, language of instruction policy, procurement and distribution challenges, TLM development and production and their availability, management and usage in schools. It also looks at the role of information and communication technology (ICT) based TLMs and their availability. The study recognizes that improved TLM system management is a critical component in achieving affordable and sustainable TLM provision for all students. This study, which draws from more than 40 Anglophone, Francophone, Lusophone, and Arabic-speaking countries will be particularly useful for policymakers, development partners, and other stakeholders attempting to understand the wide range of issues surrounding the complexity of textbook provision in Sub Saharan Africa.